WORKING CAPITAL, FIRM SIZE, SOLVABILITY, AND LIQUIDITY TOWARDS PROFITABILITY OF THE CONSUMER GOODS INDUSTRY - Kristania Victoria Simbolon; Jeanet Kathlen Salindeho; Aldo Franco Karinda (Faculty of Economics and Business, Universitas Klabat, 2022)
Studies in financial performance have been subject to debates due to different results between these variables. In some cases, the effect of the working capital, firm size, solvency, and liquidity varies across industries. This study examined the impact of working capital, firm size, solvency, and liquidity on profitability. The samples were taken from 83 listed companies in the consumer goods sector on the Indonesia Stock Exchange for 2017 – 2019. The data in this study was obtained from financial reports provided through IDX or the company's website. This research used quantitative approach with multiple linear regression analysis. Our results showed that working capital and company liquidity did not affect profitability. Meanwhile, firm size and solvency both influence profitability. Keywords: Firm Size, Leverage, Liquidity, Profitability, Working capital